Creatio Ex Amore Dei: Creation out of Nothing and God’s Relational Nature - Youngs, Samuel J. (The Asbury journal, 2014)
The opinion of many feminist thinkers and process theologians has been that Christianity needs to shed its allegiance to a God conceived in terms of omnipotent sovereignty. As an alternative, many of them have envisioned God in more relational categories, focusing on the metaphysically "limited" nature of God, with the first step along this path often being a refutation of the traditional doctrine of creatio ex nihilo. This essay summarizes such critiques before proceeding to argue that a robust understanding of creatio ex nihilo, viewed through the lens of kenosis, can actually speak more effectively to God’s relational nature and sacrificial love.